Pengaruh Kepemimpinan terhadap Motivasi dan Dampaknya pada Kinerja Pegawai Yayasan Hasyim Asy’ari Turen Malang - Kholifatul Jannah, Isro; Sinollah; R.M. Mahrus Alie (Jurnal Bisnis Islam dan Kewirausahaan, 2024)
This research aims to describe and discuss the influence of leadership on motivation and its impact on the work performance of the Hasyim Asy'ari Turen Malang Foundation employees. To be able to answer these objectives, this research uses a quantitative approach with path analysis. The research results show that: leadership has a significant effect on motivation; leadership has no significant effect on work performance; work motivation has a significant effect on employee performance and; Leadership does not have a significant effect on employee performance through work motivation. For this reason, the Hasyim Asy'ari Turen Malang Foundation must maintain employee work motivation because it has been proven to have a significant effect on performance, but leadership which can influence employee behavior must be improved